2022
DOI: 10.3390/app12042123
|View full text |Cite
|
Sign up to set email alerts
|

Mass Flow Scaling of Gas-Assisted Coaxial Atomizers

Abstract: This study aims to derive basic principles for liquid mass flow scaling of gas-assisted coaxial nozzles. Four liquid mass flow steps were investigated in the range of M˙liq = 20–500 kg · h−1, applying four atomizers with similar geometry designed at Weaero= const. High-speed camera and phase Doppler anemometer were utilized to detect the local droplet size distribution. To estimate a reliable measurement plane, a detection method and determination according to the free jet theory was used. The resulting drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…For comparion, the simulated spray patterns of the atomizers of Case 1 and the optimum case are shown in Figure 12, together with that of the experiment of the optimum atomizer. Figure 12a In comparison, the results of Li et al (2019) [8] give the opening angles of about 32 • (experiment) and 26 • (simulation by Euler-Lagrange method), respectively, and are smaller than the present corresponding findings of 45 • (simulation) and 42 • (experiment). This is expected because the gravity in their case is parallel to the jet axis; hence, the opening angle will be reduced due to down pulling of the gravity.…”
Section: Cfd Simulation Validationmentioning
confidence: 51%
See 1 more Smart Citation
“…For comparion, the simulated spray patterns of the atomizers of Case 1 and the optimum case are shown in Figure 12, together with that of the experiment of the optimum atomizer. Figure 12a In comparison, the results of Li et al (2019) [8] give the opening angles of about 32 • (experiment) and 26 • (simulation by Euler-Lagrange method), respectively, and are smaller than the present corresponding findings of 45 • (simulation) and 42 • (experiment). This is expected because the gravity in their case is parallel to the jet axis; hence, the opening angle will be reduced due to down pulling of the gravity.…”
Section: Cfd Simulation Validationmentioning
confidence: 51%
“…Ochowiak et al (2020) [4], for their two-phase conical swirl atomizers, found that the discharge coefficient and spray angle are affected by the Reynolds number, flow rate, and atomizer geometry; Yadav et al (2011) [5] showed that the droplets could be varied by changing the mass ratio of the air to liquid for their internally mixed atomizer; Chinn et al (2015) [6] observed wave patterns in the liquid film of their air-core atomizers, whereas Wang et al (2008) [7] observed flow branching and focusing in their air-assist micro-atomizer. Additionally, Wachter et al (2022) [8] developed a model to scale the liquid mass flow in gas-assisted coaxial nozzles.…”
Section: Introductionmentioning
confidence: 99%